MSCT of epithelial ovarian tumours : a pictorial illustration - Hassan, Radhiana; Abd. Aziz, Azian; Md Ralib @ Md Raghib, Ahmad Razali; Abdullah, Suhaiza (2011)
Introduction: Majority of ovarian neoplasms are benign. The classification of ovarian tumours is based on the presumed cell of origin either epithelial, germ cells or specialized gonadal stroma tumour. Among the malignant type of ovarian tumours, the epithelial type is the commonest comprising about 85% of cases. The ovarian epithelial tymours include serous, mucinous, clear cell, endometrioid and Brenner tumours. Case series We retrospectively traced MSCT of epithelial ovarian tumour performed in Hospital Tengku Ampuan Afzan, Kuantan, Pahang. A total of 48 cases were included from 2008 to 2010. The images were reviewed and correlation with HPE findings was made. This pictorial illustration emphasize on different types of epithelial ovarian tumours and the MSCT findings. Conclusion MSCT can depict tumour morphology and extension. It allows attempts on differentiation of benign from malignant ovarian lesion that is important for subsequent surgical planning.